Avaliação das condições pulmonares funcionais pré radioterapia no tratamento do câncer de mama - Renata de Carvalho Schettino (2010)
The breast cancer is probably the more dreaded by women. It is relatively rare before the 35 years elderly, but above from this age group it sweats incidence grows fast and progressively. The treatment of the breast cancer consists on surgical intervention, chemotherapy, hormoniotherapy and radiotherapy. This is responsible for a greatdecrease on rate of recurrence of the breast cancer. The objective of this study was detect, across, by means of routine use of physical therapy, pulmonary functional changes resulting from systemic treatments pre radiotherapy in the treatment of breast cancer. Participated in this study 36 women with breast cancer. The assessments of pulmonary function appraised have been inspiratory capacity, vital forced capacity, respiratory strength and peak expiratory flow. Functional capacity was evaluated bytesting six-minute walk. It was observed that there is significant difference of lung conditions observed and those expected for these patients, the observed values are well below the expected. There is reduction in lung function and worsening performance in functional testing in women undergoing chemotherapy in the treatment of breast cancer. Such dysfunction worsens the functional prognosis of these women to undergoradiotherapy. Moreover, the pulmonary function variables can be evaluated with routine instruments used allowing the detection of their changes at early and viable.